Breakfast habits among school children in selected communities in the eastern region of Ghana - Intiful, F.D.; Lartey, A. (Ghana medical journal, 2014)
Breakfast is considered the most important meal of the day, yet many people skip breakfast. Studies indicate that school age children who regularly skip breakfast are not likely to concentrate in class, thus affecting school performance. This study determined the breakfast habits and nutrient contributions of the breakfast meal to the days' nutrient intake. A cross sectional study was conducted among school children (n=359) between the ages of 6-19 years in Manya Krobo in the Eastern Region of Ghana. Questionnaires were used to collect information on background characteristics and breakfast consumption habits. The 24-hour dietary recall method was used to obtain information on the children's food intake. T-test was used to compare differences between means of variables of breakfast consumers and skippers. About 85.5% of the children had breakfast on the day of interview. More boys (87.8%) consumed breakfast compared to the girls (83.1%). For those who skipped breakfast, lack of food at home or lack of no money (36.5%) was the main reason. Breakfast consumers had significantly higher energy and nutrient intakes than those who skipped breakfast (energy 2259 verses 1360 kcal, p-0.039; vitamin A 1534 verses 662 ug/RE, p=0.001; iron 22.9 verses 13.9 mg, p=0.017, zinc 9.9 verses 5.6 mg, p=0.034). The breakfast meal contributed between 32-41% of the day's energy intake, and between 30-47% of micronutrient intake. Encouraging breakfast consumption among school children is a way to ensure that they meet their daily nutrient and energy intakes.
Keywords: Breakfast; Energy; Ghana; Nutrients; School children